Beyond Memorization: An Islamic Religious Education Learning Model for the Internalization of Character Values - Rheina Dwi Eriska; Nadia Nur Naswatul Azizah; Maulana Dwi Aprilianto (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Islamic Religious Education (PAI) has an important role in shaping students’ character through the cultivation of Islamic values in educational settings. However, the learning process is still often centered on memorization and theoretical understanding, so the values taught are not always reflected in students’ daily attitudes and behavior. This article discusses the concept of beyond memorization as a learning approach that emphasizes not only knowledge acquisition, but also understanding, appreciation, and the practical application of character values in everyday life. The study uses a literature review method by examining journals, books, and other scientific sources related to PAI learning models and the internalization of character values. The findings reveal that contextual, cooperative, problem-based, and multidisciplinary learning models can make the learning process more meaningful and relevant to students’ real-life experiences. Character values are instilled through teachers’ role models, habituation, advice, the creation of a religious school culture, and continuous interaction between teachers and students. Through this approach, PAI learning functions not merely as a medium for delivering religious knowledge, but also as a means of developing religious character, discipline, responsibility, tolerance, and social awareness in facing the challenges of modern society.